Assessing the extent of traditional biomass cookstove usage and related cooking practices: evidence from rural households in Northern Nigeria - Ya'cob, Mohd Rusli; Kabir, Ibrahim; Adamu, Abdullahi; Ho Nyuk Onn @ Ariffin, Mariani; Emang, Diana (International Organization of Scientific Research (IOSR), 2018)
Rural households in many developing countries primarily use traditional biomass cookstove (TBC), but much fewer data have been collected on the extent of usage for the cookstove. The use of TBC is detrimental to the environment, health and sustainable development. Based on household survey, this study assessed the extent of TBC usage and related cooking practices among rural households in Dessert Frontline States of Northern Nigeria. The survey was performed on 392 households, who were interviewed face-to-face using structured questionnaires from November, 2016 to January, 2017. The outcomes revealed only 7.9% used kerosene as alternative cookstove while other cookstoves usage including electric, liquefied petroleum gas and improved biomass cookstoves were non-existence. The average household monthly expenses on fuel wood was N3, 433.42 ($9.54) and the average weekly cooking and fuel wood collection hours were 25.48 and 26.62 respectively. The prevalence and large extent of TBC and its related cooking characteristics exert huge burden on the environment and households. Information gathered from this study can be used by authorities and stakeholders in Nigeria to promote cookstove improvement in order to reduce health, environmental and socioeconomic problems associated with traditional biomass cookstove.